THE EFFECTIVENESS OF ACTIVE LABOR MARKET POLICIES ON THE EXAMPLE OF THE WARMIA-MAZURY PROVINCE IN POLAND - Dorota Klembowska (Acta Scientiarum Polonorum. Oeconomia, 2012)
This paper analyzes the level of expenditure on selected programs on the labor market in a regional context and the employment effectiveness of the selected programs. It also presents the results of surveys among the unemployed from the Warmia-Mazury Province. The research shows that there is no strong correlation between the labor market situation and the employment effectiveness of the active labor market programs. It follows from the research that 75% people who received a subsidy to start their own business were not entered again into the Register of the Unemployed within 3 years from getting a subsidy. In the third year from obtaining a subsidy, more than half of them continued to operate (58.6%) and every fourth company created a workplace.